(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article discusses the use of confidence intervals in modern medical research. It is shown that calculations of confidence intervals are now becoming mandatory to meet the standards of evidencebased medicine. In addition, the issues of the application of the concept of noninferiority in the analysis of the results of medical research are considered.